SAT0475 Anti-mda5 (+) clinically amyopathic dermatomyositis-associated rapidly progressive interstitial lung disease: role of hemoperfusion with polymyxin. (12th June 2018) - Selva-O'callaghan, A.; Vizcaino, C.; Ruiz-Rodriguez, J.C.; Trallero-Araguás, E.; Ramos, N.; Berastegui, C.; Gil Vila, A.; Martinez, M.A.; Solanich, X.; Ferrer, R.
Abstract : Background: Patients with clinically amyopathyc dermatomyositis (CADM) with MDA5 positive autoantibodies may develop a severe pulmonary syndrome with rapidly progressive interstitial lung disease (RP-ILD) with a bad prognosis and high mortality. Objectives: To analyse the efficacy of a therapeutic protocol that includes hemoperfusion with polymyxin B (PMX-HP) in addition to immunosuppressive treatment with tacrolimus and glucocorticoids, plasmapheresis and intravenous immunoglobulin (IVIG). Methods: We retrospectively analysed 12 (10 male) patients diagnosed with anti-MDA5 (+) CADM associated RP-ILD between 1983 and 2018. Anti-MDA5 antibodies were determined by ELISA and confirmed by blot. RP-ILD was defined as a worsening of radiologic interstitial changes with progressive dyspnoea and hypoxemia within 1 month after the onset of respiratory symptoms. From 2014 to 2018, patients (Group 1) were treated with the following protocol: pulses of methylprednisolone (500 mg/day for 3 consecutive days), tacrolimus 2 mg/12 hour, PMX-HP (Toraymyxin 20R, Toray Medical Co., Tokyo, Japan) at a flow of 100 ml/h for 3 hour once daily on two successive days, and a plasmapheresis scheme with replacement of 3.5 l of seroalbumin 5% followed by IVIG infusion (0.4 mg/kg) during 3 consecutive days and then in alternate days for 7 days more. A comparison was performed with anti-MDA5 (+) CADM associated RP-ILD patients from a historical group (Group 2). PaO2 /FiO2 (P/F) ratio was measured before and after PMX therapy. A composite endpoint that included mortality due to respiratory failure or lung transplantation was defined. Differences between pre- and post-PMX P/F values were evaluated using paired sample t -test. Results: Mean (SD) age at diagnosis was 49 (3.5) yrs, with a mean (SD) follow-up of 13 (3.9) months. Comparison between both Groups showed that 3 out of 6 (50%) patients from the Group 1 in comparison with 5 out of 6 (83.3%) from the historical group (Group 2) reached the composite end point. Mean (CI 95%) values of P/F after PMX treatment showed a significantly improvement when compared with the pre-PMX values (240 [85–396] vs. 125, 60–189 p=0.038) Conclusions: Our protocol seems to be useful at some extent in anti-MDA5 (+) CADM associated RP-ILD patients. A transient but significant improvement can be attributed to PMX-HP. Adsorption and elimination of inflammatory cytokines, mediators and activated leukocytes, as well as anti-MDA5 antibodies could be the rationale of its efficacy. Disclosure of Interest: None declared